2019
DOI: 10.1016/j.jbiomech.2018.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a passive exoskeleton on the mechanical loading of the low back in static holding tasks

Abstract: With mechanical loading as the main risk factor for LBP in mind, exoskeletons are designed to reduce the load on the back by taking over a part of the required moment. The present study assessed the effect of a passive exoskeleton on back and abdominal muscle activation, hip and lumbar flexion and on the contribution of both the human and the exoskeleton to the L5/S1 net moment, during static bending at five different hand heights. Two configurations of the exoskeleton (LOW & HIGH) differing in angle-torque ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
118
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(157 citation statements)
references
References 30 publications
11
118
0
1
Order By: Relevance
“…Additionally, differences can be due to lower absolute moments and absence of device hysteresis in static conditions. Indeed, in static bending with the same devices, larger relative effects were found (Koopman et al, 2019). In lifting, during peak compressive loading the movement is upward and therefore peak support of the exoskeletons is 10 Nm lower than expected (Figure 2).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Additionally, differences can be due to lower absolute moments and absence of device hysteresis in static conditions. Indeed, in static bending with the same devices, larger relative effects were found (Koopman et al, 2019). In lifting, during peak compressive loading the movement is upward and therefore peak support of the exoskeletons is 10 Nm lower than expected (Figure 2).…”
Section: Discussionmentioning
confidence: 78%
“…Several exoskeletons, including the exoskeleton tested in the current study, have shown reductions of back muscle activity by 10% to 40% during static holding tasks Kobayashi and Nozaki, 2008;Koopman et al, 2019;Ulrey and Fathallah, 2013a, b). However, in dynamic lifting, peak L5S1 moments are much higher, and can reach for instance 250 Nm when lifting a 15 kg box (Kingma et al, 2001), compared to about 120 Nm in static forward bending without a load (Koopman et al, 2019). If the support level of the exoskeleton cannot be adapted to the high demand in lifting, the relative support provided by an exoskeleton will be much lower during lifting compared to static bending.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Several studies tried to extract the relationship between torques and angles of the hip [23, 24] or other lower body joints [64, 65] by assuming linear slop as quasi-stiffness between moments and angles. These researches are useful to design passive exoskeleton or prosthesis [66, 67]. However, active exoskeletons or prosthesis are capable to use a more advanced approach to generate required torques [68, 69].…”
Section: Discussionmentioning
confidence: 99%